Combined electrocoagulation and electrochemical treatment on BDD electrodes for simultaneous removal of nitrates and phosphates. Issue 6 (December 2020) - Ghazouani, Mouna; Bousselmi, Latifa; Akrout, Hanene
Graphical abstract: Highlights: Simultaneous nitrates and phosphates removal by EC process on mild steel electrodes. Parallel reduction of NO3 − on mild steel cathode led to NH3 as main by-product. Combined EC to ET on BDD enhances the removals of the remained NO3 − and NH3 . PO4 3− kinetic adsorption fitted the pseudo 2 nd order while NO3 - fitted the pseudo 1 st order. Nitrates reduction on mild steel and on BDD fitted the pseudo-first order. Abstract: The present study investigates the combination of electrocoagulation (EC) and electrochemical treatment (ET) for a simultaneous removal of nitrates and phosphates from synthetic wastewater. In the EC process, four parallel mild steel electrodes in a batch reactor were used. The increase of the current density from 1 to 40 mA cm −2 led to a total removal rates of both nitrates and phosphates at natural pHs (6 and 7). However, at high current density a rise of the electric energy consumption from 0.32 kW h m -3 for 1 mA cm −2 to 105.78 kW h m− 3 for 40 mA cm −2 was recorded. Whereas the EC process is an inefficient method that generated ammonia as by-product, which needs additional treatment. ET process using boron doped diamond (BDD), which was evaluated as one of the most promising methods for the removal of nitrogenous compounds. Combining the two processes offers a practical hybrid treatment. Such combination resulted in the oxidation of the elector-generated ammonia and therefore enhanced the final quality of the treated wastewater. Additionally, the combined EC-ET method offer a low energy consumption per unit of removed pollutant (about 0.99 kW h (kg-N) −1 ). The kinetic modeling showed that phosphates adsorption fit the pseudo-second order, while nitrates fit the pseudo-first order. However, the nitrogenous products oxidation/reduction fit the pseudo-first order on mild steel as well on BDD electrodes.